(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
Current study analyses the relationships between working capital management and profitability for Kazakhstan firms. Previously no studies have been conducted on the same topic in Kazakhstan, and therefore there is no available empirical evidence on the issue. The analyses are based on the OLS regression and covariance analysis applied to the sample of 133 firms listed in Depositary of Financial Statements. The empirical results found the significant relationship between working capital management and firms’ operating performance. Firms with better working capital management determined by shorter cash conversion cycle were more profitable than those with longer cash conversion cycle. The results of the study indicate that owners and managers of firms can improve overall operating efficiency and profitability by reducing cash conversion cycle to the reasonable minimum: avoid excessive inventory balances, decrease receivables collection period, and defer payments to suppliers. The study contributes to the existing literature by examining the effect of working capital management on profitability in the context of the emerging market of Kazakhstan.